1985
DOI: 10.1152/jappl.1985.59.5.1369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 71 ATA He-O2 on organ blood flow in the rat

Abstract: Cardiac output and organ blood flow to major organs were investigated in awake rats at 1 atmosphere absolute (ATA) air and at 71 ATA He-O2. Radioactively labeled microspheres [15 +/- 1 (SD) micron] were injected into the left ventricle during constant-rate arterial blood sampling at 1 ATA air and subsequently at 71 ATA He-O2. Intra-arterial blood pressure was continuously recorded. The partial pressure of O2 was kept between 0.4 and 0.6 ATA. The results indicate that the mean blood pressure, heart rate, cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Similar matching changes were observed in both groups, although the P a CO 2 increased only in the rats of group 2. The raised SBP cannot be associated with HBO alone, as suggested by Torbati (1987), since a similar rise has been found to occur in normoxic hyperbaric environments (Aanderud et al 1985;Hordnes and Tyssebotn 1985;Stuhr et al 1993;Bergù and Tyssebotn 1995c). On the other hand, f c was only reduced in the hyperoxic atmosphere and may be caused by a direct O 2 eect on the chemoreceptors.…”
Section: Kpa Ambient Pressurementioning
confidence: 58%
See 4 more Smart Citations
“…Similar matching changes were observed in both groups, although the P a CO 2 increased only in the rats of group 2. The raised SBP cannot be associated with HBO alone, as suggested by Torbati (1987), since a similar rise has been found to occur in normoxic hyperbaric environments (Aanderud et al 1985;Hordnes and Tyssebotn 1985;Stuhr et al 1993;Bergù and Tyssebotn 1995c). On the other hand, f c was only reduced in the hyperoxic atmosphere and may be caused by a direct O 2 eect on the chemoreceptors.…”
Section: Kpa Ambient Pressurementioning
confidence: 58%
“…Previous results have demonstrated that f c and c do not change during normoxic exposures (Aanderud et al 1985;Hordnes and Tyssebotn 1985;Risberg et al 1990;Bergù and Tyssebotn 1995c). However, if P a O 2 is elevated, f c and c are lowered (Bergù et al 1988;Tyssebotn 1992a, 1995a, b;Risberg et al 1995).…”
Section: Kpa Ambient Pressurementioning
confidence: 94%
See 3 more Smart Citations